Criminal law and the need to philosophy - عبد الله, فراس عبد المنعم (Journal of Legal Sciences, 2019)
This is a philosophical statements regrading the structural and functional ponds between criminal law and philosophy.          Aiming to prove the practical value of philosophy regarding the question of the true nature of law in general and criminal justice – law in particular.          We try to revel the deepest connections that shape the fundamental character us tics of law in reality far from the misunderstanding general by social, political and cultural influences that affection negatively the efficiency of the law.          The elementary question of the study is how to use philosophy to understand the true nature of law and creating implementing the just law.          In order to achieve this goal we emphasis the concept of scientific logical law instead of metaphysical, ideological, and positivism approaches that proves its unsuffincy to provide stable and practical concept of law.          The first step towards constracting valid and modern model of law is to separate the true matters of law (Legal facts) from falsehood and pretense added to law through cultural and political influences.          Law according to philosophy is distinct system vegulating social environment not social relations. The later is mere product of social environment. So its very logical for the law to target the environment instead of its by product (Relations).          More philosophical examination of law are nedeeded and less juris prudence.